Farm wage and rice price dynamics in Bangladesh - Md. Fuad Hassan; Lukas Kornher (University of Bonn, Center for Development Research (ZEF), 2019)
Concepts explaining the wage-price nexus in Bangladesh are diverse and conflicting. A proper understanding of the relationship between food prices and rural wages is essential for planning policies in support of the rural poor. In exploring the link between food prices and rising agricultural wages, this study analyzes the dynamic relations between those two by using monthly data from 1994 to 2014. A standard vector error correction model (VECM) is implemented to determine the short-run and long-run relationships between wages and food prices in eight divisions in Bangladesh. In addition, we use autoregressive distributed lag (ARDL) models to estimate the pass-through coefficients and to compare the short-run effects of rice price and urban wage shocks on agricultural wages. We find statistical evidence for a structural break between January 2007 and January 2009 in the relationships of the variables in all divisions. After the structural break, in six out of eight divisions, any shock in rice prices does not transmit to the farm wages in the short-run. Moreover, our findings show that in the long-run food prices have become less influential in explaining the changes in rural wages while the influence of urban wages has become stronger in some divisions.
Keywords: Q11; J21; J31; 330; Agricultural Wages; Lewis Transformation; Rural labor markets; Bangladesh